SUSTAINABLE SOLUTIONS: SMART IRRIGATION FOR PRECISION AGRICULTURE AT WIWANDA AGROW - Kumaradewi M, Ni Putu Dhanan; Anak Agung Adi Wiryya Putra; Kadek Adyatna Wedananta (Bajang Institute, 2025)
This community service initiative addresses environmental and agricultural challenges in Pancasari Village, Bali, by transforming organic waste into eco enzyme an environmentally friendly solution for organic farming. The primary goal is to reduce organic waste, improve soil health, and support sustainable agriculture through smart irrigation practices at Wiwanda Agrow. The method included environmental observation, public education sessions, eco enzyme production workshops, and communal clean-up activities. Results demonstrated increased community awareness and capability in waste management and organic agriculture. The initiative not only promoted sustainable waste processing but also boosted local tourism and economic opportunities through eco enzyme applications in farming and water purification.